2019
DOI: 10.1097/dad.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Confocal Microscopy Features of Plaque Psoriasis Overlap With Horizontal Histopathological Sections: A Case Series

Abstract: Reflectance confocal microscopy (RCM) displays horizontal, en face tissue sections of the epidermis and upper dermis, and interpretation of its features is classically based on the comparison with vertical conventional histopathological sections that, as known, do not reflect the same plane of observation. In 10 patients affected by psoriasis, we correlated RCM images with horizontal histopathological sections from skin biopsies, observing in all cases marked overlaps between the 2 techniques. Although vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…This typical mast cell infiltrate is one of the four mastocytosis diagnostic patterns described above. Of note, HHS, which shares with RCM the en face view of the skin, confirms to strongly correlate with RCM findings, as already described in other inflammatory and neoplastic skin disorders 7‐9 …”
Section: Figuresupporting
confidence: 79%
“…This typical mast cell infiltrate is one of the four mastocytosis diagnostic patterns described above. Of note, HHS, which shares with RCM the en face view of the skin, confirms to strongly correlate with RCM findings, as already described in other inflammatory and neoplastic skin disorders 7‐9 …”
Section: Figuresupporting
confidence: 79%
“…Reflectance confocal microscopy revealed, at superficial layers after a few horizontal scans, rounded dark areas with central structures containing bright elements in real‐time motion, interspersed among epidermal keratinocytes arranged in a honeycomb pattern (c). At horizontal histopathology sections of the same fields, the dark areas corresponded to the tips of numerous, enlarged, superficialized dermal papillae containing dilated/tortuous capillary loops (d; haematoxylin and eosin, original magnification × 100), resulting from papillomatosis with thinning of the suprapapillary plate . Our study demonstrated overlapping morphological changes underlying the clinical Auspitz sign, in horizontal histopathology sections, videodermatoscopy and reflectance confocal microscopy imaging.…”
supporting
confidence: 54%
“…24 Another non-invasive technique that has been reported to improve the diagnosis of genital psoriasis is in vivo reflectance confocal microscopy (RCM), which is currently used in the evaluation of melanocytic lesions, skin tumors, and some inflammatory and infectious diseases. 30,31 In a study on 10 patients with biopsy-proven psoriatic balanitis, handheld RCM revealed a peculiar pattern, consisting of enlarged, irregular, blurred and dark ("non-rimmed") dermal papillae filled with dilated blood vessels and separated by thin interpapillary rete ridges. 29 This pattern correlates with the "red dots"/"bushy capillaries" observed at dermoscopy.…”
Section: Diagnosismentioning
confidence: 99%